American history through Hollywood film : from the Revolution to the 1960s - Stokes, Melvyn (London : Bloomsbury Academic, 2013)
This title offers a new perspective on major issues in American history from the 1770s to the end of the 20th century and explores how they have been represented in film.
Includes bibliographical references (pages 231-281) and index.
Keywords: Historical films -- United States -- History and criticism